Developing and Delivering a Remote Experiment based on the Experiential Learning framework during COVID-19 Pandemic - W.D. Kularatne; Lasanthika H. Dissawa; T.M.S.S.K. Ekanayake; Janaka B. Ekanayake (International Journal of Asian Education, 2022)
The students following Engineering disciplines should acquire a conceptual understanding of the concepts and the processors and attitudes. There are two recognizable learning environments for students: classroom and laboratory environments. With the COVID-19 Pandemic, both environments merged to online environments, impacting students' processes and characteristic attitudes development. This paper introduces a theoretical framework based on experiential learning to plan and deliver processes online. A case study based on the power-factor correction experiment was presented. The traditional experiment that runs for 2 hours was broken into smaller tasks such as pre-lab activity, simulation exercise, PowerPoint presentation, remote laboratory activity, and final report based on the experiential learning approach. The delivery of the lab under online mode delivery was presented. Then students' performance was compared before and after the online mode of delivery. It was found that students' performance on average has a distinct improvement. In order to obtain students' reflections about the online experiential learning approach, a questionnaire that carries close and open-ended questions was administered. The majority of the students liked the approach followed and praised for allowing them to experiment in a novel way during the COVID-19.